Development and Application of Software for Estimating the Source of Food-poisoning - WADA, Masamichi; SHIOZAWA, Kanji (Japanese Journal of Food Microbiology, 1995)
When food-poisoning occurs, the source of the foodstuff has been determined by manually comparing the prevalence of patients with and without certain foods, using chi-square test. The increase in the rate of patients with food-poisoning and in the sources of foodstuff suggest that the development of a simpler method of more quickly and accurately analysing potential sources is required. We developed software for estimating the source of foodstuffs from a master-table using a questionnaire to determine whether a subject is a patient, and whether he has consumed the foodstuff or not. The data are then analyzed by statistical methods on a personal computer . The software is sufficient to analyze foodstuffs during large scale food-poisoning using a combination of chi-square test, Fisher's exact test and t-test. Statistical expertise is not required to operate the software and anyone can determine the source of food-poisoning . Thus, this software may facilitate the investigation of the source when food-poisoning occurs.